Способ разделения изотопов - Афанасьев В. Г. Владимир Григорьевич; Водолазских В. В. Виктор Васильевич; Гаврилов П. М. Петр Михайлович; Журин В. А. Владимир Анатольевич; Калашников А. Л. Анатолий Леонидович; Колесников А. И Анатолий Иванович; Короткевич В. М. Владимир Михайлович
опубл. 20.08.08